Composite beams with indented construction joint – comparison of results of laboratory tests and numerical analysis - Sadowski, Grzegorz; Wiliński, Piotr; Halicka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The paper presents a comparative analysis of the behaviour of a composite beam, consisted of a precast element with indented surface and new concrete layer, subjected to 4-point bending. The results obtained from the virtual model of the beam created using the finite element method (Abaqus/CEA 2019 software) were compared with the laboratory test results obtained with use of the digital image correlation (DIC) method for identifying the crack pattern. The virtual model of composite beam was calibrated by the choice of interface parameters ensuring that the value of load resulting in delamination between concrete layers was close to that value obtained in the laboratory tests. The comparative analysis showed that the pattern of bending and shear cracks and the pattern of interface crack obtained with the finite element method reflect the laboratory test results properly. It can be assumed that the crack between concrete layers is related to the appearance and propagation of shear cracks. On the basis of FEM analysis it can be concluded that the phenomena identified as “shear friction” and “dowel action” are significantly activated after the interface cracking.